The Influence of Voluntary Disclosure Program (VDP), Tax Sanctions, and Tax Socialization on Individual Taxpayer Compliance at KPP Pratama Jakarta Kalideres - Syahrial, Irzan; Haryanto, Pandu; Handari, Henni; Hidayat, Malik; Aditya, Marcellinus (Dinasti International Journal of Management Science, 2025)
Tax revenue is the primary source of income for Indonesia, supporting national development. However, taxpayer compliance remains a significant challenge. The Voluntary Disclosure Program (VDP), tax penalties, and tax socialization are expected to improve taxpayer compliance. This study aims to analyze the effect of VDP, tax penalties, and tax socialization on individual taxpayer compliance at the Jakarta Kalideres Tax Office (KPP Pratama Jakarta Kalideres). This research uses a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 30 individual taxpayers registered at the Jakarta Kalideres Tax Office. Multiple linear regression analysis was performed using SPSS software. The results show that VDP significantly and positively impacts taxpayer compliance, with a regression coefficient of 0.45 (p<0.05). Tax socialization also has a significant positive effect, with a coefficient of 0.38 (p<0.05). However, tax penalties have a positive but not significant effect, with a coefficient of 0.12 (p>0.05). Collectively, the three independent variables explain 65% of the variation in taxpayer compliance (Adjusted R²=0.65). VDP and tax socialization effectively improve taxpayer compliance, while the effectiveness of tax penalties requires further evaluation.